A Study On Personal Career Growth And Postgraduate Enrollment With Scholarship A Ward As The Moderating Effect: Experiences In Universiti Sains Malaysia - Baba Rahim , Norizan (2010)

(untitled)
This research study was mainly focus on. the relationship between academic achievement, financial capacity and working experience with postgraduate enrollment and scholarship awards provided by Institute of Graduate Studies, Universiti Sains Malaysia as the moderating effect. It is about to examine which dimension of the personal career growth has the highest weightage towards the postgraduate enrollment and does the scholarship award give any significant as the moderating effect. Kajian ini memberi tumpuan utama kepada perhubungan diantara kecermelangan academik, kemampuan kewangan dan pengalaman kerja terhadap pendaftaran pelajar ijazah tinggi di Universiti Sains Malaysia bersama bantuan kewangan sebagai faktor pengerat. Ia sebenarnya adalah untuk untuk memgukur mana satu dimensi diantara faktor kelayakan peribadi yang mempunyai pengaruh yang tertinggi terhadap pendaftaran pelajar ijazah tinggi dan adakah bantuan kewangan memberikan kesan yang besar sebagai faktor pengerat.